Antihistamines, phenothiazine-based antipsychotics, and tricyclic antidepressants potently activate pharmacologically relevant human carbonic anhydrase isoforms II and VII. (31st December 2023) - Fiorentino, Francesco; Nocentini, Alessio; Rotili, Dante; Supuran, Claudiu T.; Mai, Antonello
Abstract: Carbonic anhydrases (CAs) are important regulators of pH homeostasis and participate in many physiological and pathological processes. CA activators (CAAs) are becoming increasingly important in the biomedical field since enhancing CA activity may have beneficial effects at neurological level. Here, we investigate selected antihistamines, phenothiazine-based antipsychotics, and tricyclic antidepressants (TCAs) as potential activators of human CAs I, II, IV, and VII. Our findings indicate that these compounds are more effective at activating hCA II and VII compared to hCA I and IV. Overall, hCA VII was the most efficiently activated isoform, particularly by phenothiazines and TCAs. This is especially relevant since hCA VII is the most abundant isoform in the central nervous system (CNS) and is implicated in neuronal signalling and bicarbonate balance regulation. This study offers additional insights into the pharmacological profiles of clinically employed drugs and sets the ground for the development of novel optimised CAAs.